Nonfatal Strangulation in a Sample of Domestically Violent Stalkers: The Importance of Recognizing Coercively Controlling Behaviors - Bendlin, Martyna (Criminal justice and behavior, 2019)
Strangulation is different to other types of physical violence as it often leaves no visible injuries and is frequently motivated by coercive control. Few studies have explored nonfatal strangulation and coercive control, and no studies have explored these factors within a sample of stalkers. Given that stalking perpetrators exhibit many of the coercively controlling behaviors related to nonfatal strangulation, the current study explored nonfatal strangulation and other coercively controlling behaviors in a stalking sample. A police dataset of 9,884 cases of domestic violence that involved stalking was analyzed. Results revealed that coercive control and related behaviors of excessive jealousy, victim isolation, victim fear, and victim’s belief that the perpetrator will kill them were associated with higher likelihood of having experienced nonfatal strangulation. These results may help first responders to identify victims at risk of nonfatal strangulation and suggest a need for nonfatal strangulation to be a criminal offense.